Physiological issues surrounding the performance of adolescent athletes - Naughton, G.; Farpour-Lambert, N. J.; Carlson, J.; Bradney, M.; van Praagh, E. (Sports Medicine, 2000)
More than ever, many young athletes are being encouraged to train intensely for sporting competitions from an early age. Compared with studies in adults, less is known about the physiological trainability of adolescents. The velocity of physical growth during the adolescent years makes research with a group of young athletes particularly difficult. The purpose of this review is to discuss a number of physiological issues that surround the performances of the adolescent athlete. Research has highlighted the role of growth hormone (GH) in the abrupt acceleration of linear growth that occurs during adolescence. In addition, GH has been shown to be sensitive to exercise following short term intervention studies. The reduced anaerobic power of the adolescent athlete compared with that of an adult athlete has been attributed to the intrinsic properties of the muscle that are yet to be fully understood. Resistance training studies in male adolescents, and to a lesser extent female adolescents, highlight the substantial relative strength gains that can be obtained. Aerobic trainability in young boys appears to improve markedly during the adolescent years. One of the most plausible explanations for this observation is the 'trigger hypothesis' which links increased aerobic improvements in adolescence with hormonal changes and substantial growth of the cardiorespiratory and musculoskeletal systems. Studies of aerobic trainability in adolescent girls are too scarce to be conclusive. An understanding of the impact of long term intensive training on adolescent athletes is difficult to ascertain because physical stresses vary both between and within sports. There is, however, limited evidence to suggest that 'intense' training does not impair normal growth, development or maturation. Adolescent athletes who experience rapid growth as well as large increases in training volumes may be vulnerable to overuse injuries.